Site- and house-specific and meteorological factors influencing exchange of particles between outdoor and indoor domestic environments. (August 2019) - Chiesa, Maria; Urgnani, Rossella; Marzuoli, Riccardo; Finco, Angelo; Gerosa, Giacomo
Abstract: The aim of this study was to investigate the influence of site- and house-specific as well as meteorological factors on indoor and outdoor particle concentrations. Particle number (PN) and particle mass (PM) concentrations were monitored in 62 houses in Brescia, Northern Italy, during two winter monitoring periods. Measurements were conducted in houses of non-smokers and without the activation of any internal aerosol sources from domestic activities such as cooking and cleaning. Indoor and outdoor particle concentrations were measured for 30 min in each house. A wide-range aerosol spectrometer (MINIWRAS 1371, GRIMM) was used to detect 41 classes of particles from 10 nm to 35 μm. The effects of natural ventilation on indoor particle concentrations were also considered by measuring PM and PN indoor/outdoor ratios before and after a window was opened for a period of 15 min. An ANOVA analysis was performed on a sub-dataset of 35 houses to evaluate the dependence of PN and PM concentrations on site- and house-specific as well as meteorological factors. The house energy class was significantly related to indoor particle concentrations, and window dimensions seemed to influence the concentrations both before and after the ventilation period. We found that some factors, e.g., the floor level, need further investigation. Highlights: Indoor and Outdoor PN and PM were monitored for 62 houses in a high polluted city. With no active indoor particles sources PN and PM are higher outdoor than indoor. ANOVA evidenced that PN and PM depend on site, meteorological and building factors. Indoor UF and fine particles concentrations are lower in high energy class buildings. Indoor PN and PM depend on the surface of windows opened during natural ventilation.